Mental health in competitive sports in times of COVID-19 - Claussen, M. C.; Zimmermann, S. M.; Spörri, J.; Seifritz, E.; Scherr, J.; Fröhlich, S. (Sports & exercise medicine switzerland, 2020)
Mental health, like physical health and athletic performance, is an integral dimension of competitive sport,and all three cannot be considered independently. Mental wellbeing and athletic performance aremutually dependant. Psychological distress and disorders may have an impact on performance, increasethe risk of physical injuries and prolong rehabilitation. In turn, physical injuries limit athletic performanceand may pose a risk for sustaining mental health. These are known interrelationships. In particular, the COVID 19 pandemic and the associated restrictions may represent burdens and risks to mental health incompetitive sports and must therefore be taken into account.